Exploring player communication in interactions with sport officials - Cunningham, I.; Simmons, P.; Mascarenhas, D.; Redhead, S. (Movement & Sport Sciences - Science & Motricité, 2015)
Communication and player management are central to officiating, but player-official interaction is difficult to train and unresearched. This study interviewed team captains from different sports and used video elicitation and Goffman`s (The presentation of self in everyday life, 1959, Interaction ritual: Essays in face-to-face behaviour, 1967) dramaturgical sociology of social interaction to explore ways players interact and attempt to influence officials. Players were found to behave irrationally sometimes, but mostly they are strategic. Player attitudes to interactions range from fatalistic acceptance to whatever the official decides, through selective complaint, to continuous opportunism. Players attempt to influence officials directly and indirectly through complaining, questioning, flattery or praise. These findings deepen our understanding of the balance - between authority, accountability and respectfulness - that characterises effective communication and interaction with players.